Some scleractinian corals (Scleractinia: Anthozoa) of Larak Island, Persian Gulf - Samiei, Jahangir Vajed; Dab, Koosha; Ghezellou, Parviz; Shirvani, Arash (Zootaxa, 2013)
There is a shortage of knowledge about taxonomy and distribution of coral reef communities in the Persian Gulf. One of the main steps in the conservation and evaluation of such an environment is to locate and identify the communities and their inhabited fauna and flora. In the present study scleractinian corals were collected from depths of 3 to 9 meter around Larak Island, Persian Gulf. Underwater photographs of the sampled specimens were obtained in the natural habitat before sampling. 37 species have been identified via morphological characteristics of exoskeletons. The following study provided a pictorial reference to enhance the basic knowledge about coral reef communities in the Persian Gulf.